2008
DOI: 10.1001/archotol.134.9.993
|View full text |Cite
|
Sign up to set email alerts
|

Rectangle Tongue Template for Reconstruction of the Hemiglossectomy Defect

Abstract: To determine if a rectangular template free tissue transfer is effective for the reconstruction of the hemiglossectomy defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 8 publications
0
51
0
2
Order By: Relevance
“…6 A distinction was further made between tongue defects of 66 percent (group B1) and 75 percent (group B2) in group B, whereas most authors would classify them into subtotal tongue defects. 8,12,23,26,30,37,49 The additional division between groups B1 (66 percent resected) and B2 (75 percent resected) allowed further refinements in flap selection. For group B2 defects, the small amount of remaining tongue (approximately 25 percent) probably has no functional role but plays an important part in maintaining the anatomical integrity of the base of the tongue, the retromolar Plastic and Reconstructive Surgery • December 2010 trigone, or one side of the pterygoid fossa, depending on its location.…”
Section: Discussionmentioning
confidence: 99%
“…6 A distinction was further made between tongue defects of 66 percent (group B1) and 75 percent (group B2) in group B, whereas most authors would classify them into subtotal tongue defects. 8,12,23,26,30,37,49 The additional division between groups B1 (66 percent resected) and B2 (75 percent resected) allowed further refinements in flap selection. For group B2 defects, the small amount of remaining tongue (approximately 25 percent) probably has no functional role but plays an important part in maintaining the anatomical integrity of the base of the tongue, the retromolar Plastic and Reconstructive Surgery • December 2010 trigone, or one side of the pterygoid fossa, depending on its location.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the patients have difficulty in deglutition and protrusion of their tongue. Chepeha and his colleagues [9] reported that tongue protrusion greater than 0.8 cm is associated with better swallowing results in the tongue reconstruction of the hemiglossectomy defect. So the operators should suture the flap to the tongue, pulling the tongue to the protruding position out of a glossoptotic position.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the volume of the flap for the defects of hemiglossectomy, there was some reports that discuss whether the reconstruction with flap is necessary or not [10,11], but most papers describe that reconstruction with free flap provide good functional results [1][2][3][4][5][6][7][8][9]. The flaps seen in these papers are comparatively large, and the size of reconstructed tongues is as large as that of original tongue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Options of free tissue transfer for tongue reconstruction include the rectus abdominis myocutaneous fl ap, latissimus dorsi myocutaneous fl ap, radial forearm fl ap (RFFF), and more recently, the ulnar forearm and the anterolateral thigh fl ap (ALTF), and the medial sural artery perforator fl ap. [6][7][8][9][10][11][12][13][14][15][16][17] In our hospital, we have successfully used the PMMF for reconstruction of total glossectomy defects.…”
mentioning
confidence: 99%